The contribution of specialized sports press in spreading sports financing culture among Algerian professional football teams - Zouaoui, Abdelouahab; Mendjehi, Makhlouf; Bouslah, Nadir (Journal of Human Sciences, 2022)
The research aims to know the importance of the Algerian specialized sports press and the extent of its contribution to spreading of sports funding culture among the Algerian professional football teams. The survey study was conducted on sports journalists in the province of Algiers. We adopted the descriptive approach, which aims to collection of information, its organization and its description. We used a questionnaire included a set of questions divided into three axes and distributed to 25 journalists, which constitute a representative sample of the study community composed of 80 journalists from "El-Haddaf newspaper” , El Khabar Erriadi newspaper” and “Le Buteur. "After the procession of the results of the questionnaire using the Statistical Package for the Social Sciences (SPSS), the study concluded to the following results: The specialized sports press contributes to spreading the culture of sports funding among Algerian professional football teams , through the introduction of sports funding laws and the presentation its types of sources.